P2.005 Giant Condyloma Acuminata of Buschke and Lowenstein Treated Successfully Surgically. (13th July 2013) - Puri, N; Talwar, A
Abstract : Introduction: The Buschke Lowenstein tumour is an extremely rare, slow-growing, locally destructive, cauliflower-like mass, also known as giant condyloma acuminata. Case Report: We report a case of a 42 year old male who presented to the department of surgery with perineal tumour since two years. The mass was painless initially but later became painful. On local examination, the ano perineal region of the patient was completely occupied by a cauliflower like tumour with multiple fistulae. After histopathological confirmation, the tumour was removed surgically, as it was resistant to medical treatment. Radical surgery was attempted. The tumour was found to be very vascular and deeply infiltrating. Wide local resection of the perianal tissue was performed Discussion: Histopathology of BLT shows blunt-shaped masses of tumour project deeply into the dermis and contiguous structures. The tumour cells have little evidence of atypia and are not found inside blood vessels or lymphatics. Individual keratinocytes may show keratinization, but no horn pearls are seen. Lymphohistiocytic inflammation is usually present. Conclusion: Troublesome recurrences of BLT occur frequently and a propensity for infection and fistula formation is common. Regardless of the size and origin of BLTs, gaining early control of the disease using wide, radical surgical excision provides the best overall rate of survival.